Cross-shelf transport of high chlorophyll-a coastal waters by frontal eddies in the south of Java sea - Azis Ismail M.F.; Budiman A.S.; Basit A. (Kuwait Journal of Science)
Intense mesoscale eddy activity has been observed off the southern Java coast (SJC), yet its impact on local ecosystems remains largely unknown. To investigate this, we examined remotely sensed altimetry, chlorophyll-a (Chl-a), and sea surface temperature (SST) data, focusing on their response to eddies in the region. Our eddy detection and tracking analysis revealed a unique cyclonic frontal eddy near the SJC coast and a large anticyclonic eddy offshore, active from July to September 2019. The cyclonic frontal eddy induced water transport through eddy filaments, upwelled subsurface cold water, and enhanced Chl-a concentrations by horizontally entraining Chl-a-rich shelf water offshore. The anticyclonic eddy then contributed to further distributing this enriched water southward. The mean cross-shelf transport associated with the frontal eddy was estimated at 1.80–2.33 Sv offshore, exporting approximately 1.87–2.40 × 103 tons of Chl-a to the Indian Ocean during its lifetime. Additionally, the spatial cross-correlation analysis of zonal and meridional wind stress with Chl-a revealed relatively high correlation values (0.6–1) and short lag times (<5 days) in offshore areas, indicating that the role of wind in the Chl-a advection cannot be ignored. We propose a three-stage mechanism to explain the presence of high Chl-a offshore:1) Wind-driven upwelling intensifies coastal nutrients, elevating Chl-a concentrations in coastal waters, 2) Frontal cyclonic eddy facilitates the retention and offshore export of these upwelling-enriched waters. and 3) Anticyclonic eddy advects these nutrient-rich waters further south. The combination of enhanced coastal upwelling and eddies can explain nutrient-rich coastal waters in offshore regions. © 2024 The Authors